The Distributive Effects of Land Titleon Labor Supply : Evidence From Brazil - Moura, Mauricio (IMF Working Papers; Working Paper, 2011)
This paper studies the effects of property-titling on labor supply. The role of legal ownership security is isolated by comparing the effect that being part of, or excluded from, a land title program in a unique quasi-experiment in two similar communities in the Brazilian city of Osasco. Our main innovation is the estimation of the distributive impact of land title on hours worked via the quantile regression methodology and the weighting estimator of Firpo (2007). The estimates suggest that the impact of land-titling on labor supply is heterogeneous and greater for those households with fewer hours worked before the program.